Globalization and the Role of Public Transfers in Redistributing Income in Latin America and the Caribbean - Skoufias, Emmanuel; Lindert, Kathy; Shapiro, Joseph (2012)
This paper focuses on measuring the extent to which publicly subsidized transfers in Latin America and the Caribbean redistribute income. The redistributive power of 56 transfers in eight countries is measured by their simulated impacts on poverty and inequality, and by their distributional characteristic. Our findings suggest that public transfers can be effective instruments to redistribute income to the poor. Despite coverage and distributional patterns that favor the poor, small unit subsidies limit the redistributive, poverty and inequality impacts of even the most targeted social assistance programs.